Toward a better understanding of fish‐based contribution to ocean carbon flux. Issue 5 (17th February 2021) - Saba, Grace K.; Burd, Adrian B.; Dunne, John P.; Hernández‐León, Santiago; Martin, Angela H.; Rose, Kenneth A.; Salisbury, Joseph; Steinberg, Deborah K.; Trueman, Clive N.; Wilson, Rod W.; Wilson, Stephanie E.
Abstract: Fishes are the dominant vertebrates in the ocean, yet we know little of their contribution to carbon export flux at regional to global scales. We synthesize the existing information on fish‐based carbon flux in coastal and pelagic waters, identify gaps and challenges in measuring this flux and approaches to address them, and recommend research priorities. Based on our synthesis of passive (fecal pellet sinking) and active (migratory) flux of fishes, we estimated that fishes contribute an average (± standard deviation) of about 16.1% (± 13%) to total carbon flux out of the euphotic zone. Using the mean value of model‐generated global carbon flux estimates, this equates to an annual flux of 1.5 ± 1.2 Pg C yr −1 . High variability in estimations of the fish‐based contribution to total carbon flux among previous field studies and reported here highlight significant methodological variations and observational gaps in our present knowledge. Community‐adopted methodological standards, improved and more frequent measurements of biomass and passive and active fluxes of fishes, and stronger linkages between observations and models will decrease uncertainty, increase our confidence in the estimation of fish‐based carbon flux, and enable identification of controlling factors to account for spatial and temporal variability. Better constraints on this key component of the biological pump will provide a baseline for understanding how ongoing climate change and harvest will affect the role fishes play in carbon flux.